2019
DOI: 10.1007/s00706-019-02401-x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of commonly used tags on structural propensities and internal dynamics of peptides

Abstract: The influence of biotin and fluorescein tags attached to the N-terminus of peptides on their structural propensities is assessed by NMR methods. While the small peptides investigated are highly mobile with no uniquely preferred conformation, the introduction of the tags, in particular hydrophobic ones, clearly shows an influence on NMR parameters such as chemical shifts and relaxation properties, which are not restricted to the nearby residues, but also affect distant parts. Thus, long-range effects on structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…39 Furthermore, a NMR based study has also revealed the influence of commonly used tags on structural propensities and internal dynamics of peptides. 40 Importantly, the attached fluorescent dye, as an inbuilt moiety in the polypeptide chain, may influence the inherent properties of the proteins including their native conformation, their aggregation kinetics, and the morphology of their amyloid assembly. 39,40 In contrast to these unavoidable complications linked to the covalent tagging of fluorophores, our method produces stable fluorescent amyloid nanofibers without altering the aggregation kinetics and the characteristic b-structure of the amyloids (Fig.…”
Section: Application Of Rho-b-incorporated Amyloids For Experiments I...mentioning
confidence: 99%
“…39 Furthermore, a NMR based study has also revealed the influence of commonly used tags on structural propensities and internal dynamics of peptides. 40 Importantly, the attached fluorescent dye, as an inbuilt moiety in the polypeptide chain, may influence the inherent properties of the proteins including their native conformation, their aggregation kinetics, and the morphology of their amyloid assembly. 39,40 In contrast to these unavoidable complications linked to the covalent tagging of fluorophores, our method produces stable fluorescent amyloid nanofibers without altering the aggregation kinetics and the characteristic b-structure of the amyloids (Fig.…”
Section: Application Of Rho-b-incorporated Amyloids For Experiments I...mentioning
confidence: 99%
“…In this study a fully working chromatographic workflow was implemented, which allows real time monitoring of the loading, washing, and elution step. The degradation of the tag can be a result due to its super exposed nature or problems in the sequence which can lead to degradation by proteases [15, 50]. A degradation of the tag (26 kDa eGFP, 29 kDa GFP‐(RH)4) could be possible and would explain the additional band which can be seen in Figure 3A in the lysate (lane 2) and the purified fraction (lane 3).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, this assay has some limitations, in common with many widely-used autophagic flux assays, such as: the need for overexpression of the exogenous reporter, although potentially, CRISPR knock in technology could be used to overcome this [ 47 ]; the potential accumulation of TOLLES in lysosomes over time and the possibility of affecting lysosomal activity; the use of a bulky tag that can potentially affect protein function or induce aggregation [ 48 ]. Recently described Halo-tag probe-based assays for autophagic flux may circumvent the latter consideration to some degree, but the Halo-tag is still relatively bulky compared to small epitope tags, and these probes are relatively low throughput [ 45 ].…”
Section: Discussionmentioning
confidence: 99%